Introduction: Ethnomedicine and medical anthropology today, in the case of Tibet (Medicine Anthropology Theory, 2016)
This collection of essays brings to light important themes in medical anthropology that have been eclipsed in recent years by theoretical turns toward problems of suffering, experience, and ontology (among others). Namely, they remind us of the importance of what was once popularly called the study of ‘ethnomedicine’.